MEASURING TPACK SKILLS OF ELEMENTARY SCHOOL TEACHERS: READINESS TO TEACH SCIENCE IN BLENDED-LEARNING ERA - Septi Kurniasih; Muhammad Agus Hardiansyah; Ikhsanuddin Ikhsanuddin; Lukman Nulhakim (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2022)
The science learning process has changed from classroom to online education. This leads to blended learning-based learning in a relatively short amount of time today, placing many challenges and burdens on teachers. Motivation to direct the learning process is important to understand how technology can prepare teachers' abilities in the future, which is an integral part of the learning process. This study aims to measure the willingness of elementary schools in different parts of Indonesia to practice blended learning. This study is a descriptive and quantitative study. The survey was conducted although it needs improvement in mastering Technological Knowledge. So it on 64 primary school teachers with 1 to 10 years of teaching experience in 16 states of Indonesia, who are currently training in-service teachers at Sultan Agung Tirtayasa University. The survey results show that the teacher`s ability to use each component in the TPACK is generally categorized as